2007
DOI: 10.1029/2007gl031809
|View full text |Cite
|
Sign up to set email alerts
|

Rapid loss of the Ayles Ice Shelf, Ellesmere Island, Canada

Abstract: [1] On August 13, 2005, almost the entire Ayles Ice Shelf (87.1 km 2 ) calved off within an hour and created a new 66.4 km 2 ice island in the Arctic Ocean. This loss of one of the six remaining Ellesmere Island ice shelves reduced their overall area by $7.5%. The ice shelf was likely weakened prior to calving by a long-term negative mass balance related to an increase in mean annual temperatures over the past 50+ years. The weakened ice shelf then calved during the warmest summer on record in a period of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
121
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 23 publications
3
121
0
Order By: Relevance
“…MLSI typically fringed the fronts of ice shelves in the past and protected them from the open ocean, and can be considered as incipient ice shelf (Pope et al 2012). The loss of MLSI may therefore limit the potential for ice shelf regrowth under current climate conditions, and make the ice shelves more vulnerable to future climate change (Copland et al 2007).…”
Section: Ice Shelvesmentioning
confidence: 99%
See 2 more Smart Citations
“…MLSI typically fringed the fronts of ice shelves in the past and protected them from the open ocean, and can be considered as incipient ice shelf (Pope et al 2012). The loss of MLSI may therefore limit the potential for ice shelf regrowth under current climate conditions, and make the ice shelves more vulnerable to future climate change (Copland et al 2007).…”
Section: Ice Shelvesmentioning
confidence: 99%
“…Much of the 90 % decrease in ice shelf extent that has occurred since their discovery in the late 19th century coincided with a period of regional warming in the 1930s and '40s. Marked positive air temperature anomalies since the 1990s have driven further ice shelf collapse (Copland et al 2007). The complete loss of the Ayles Ice Shelf (about 87 km 2 ) in 2005 was accompanied by the loss of about 1020 km 2 of multiyear landfast sea ice (MLSI) in nearby Yelverton Bay (Copland et al 2007).…”
Section: Ice Shelvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations showed that winter freezing of the ice mélange is correlated with a decrease in the calving rate, an advance of the glacier front, and a slowing down of the ice flow (Sohn et al, 1998;Joughin et al, 2008c) and that summer decay is followed by an increase in the calving rate, a retreat of the front, and accelerated ice flow (Higgins, 1991;Copland et al, 2007). Some authors argue that ice mélange may directly resist the ice flow (Walter et al, 2012), while others suggest that it only maintains the integrity of the terminal part of the glacier (Sohn et al, 1998;Amundson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another quantity, that of ice mélange, a heterogeneous mixture of sea ice, marine ice, blown snow, and fragments of icebergs, is suspected to play an important role in the seasonal cycles of the glacier front (Higgins, 1991;Sohn et al, 1998;Reeh et al, 2001;Khazendar and Jenkins, 2003;Fricker et al, 2005;Copland et al, 2007;Joughin et al, 2008a, b, c). Observations showed that winter freezing of the ice mélange is correlated with a decrease in the calving rate, an advance of the glacier front, and a slowing down of the ice flow (Sohn et al, 1998;Joughin et al, 2008c) and that summer decay is followed by an increase in the calving rate, a retreat of the front, and accelerated ice flow (Higgins, 1991;Copland et al, 2007).…”
Section: Introductionmentioning
confidence: 99%